Properties and units in the clinical laboratory sciences. Part XXIII. The NPU terminology, principles, and implementation: A user’s guide (IUPAC Technical Report) - Petersen, Ulla Magdal; Dybkær, René; Olesen, Henrik (Pure and applied chemistry, 2012)
This document describes the application of the syntax, semantic rules, and format of the Nomenclature for Properties and Units (NPU) terminology for coded dedicated kinds-of-property in the various subject fields of the clinical laboratory sciences. The document sums up considerations and reasoning by the Committee and Subcommittee on Nomenclature for Properties and Units (C-SC-NPU) and collects the experience with the system through some eight years of application in electronic health communication. Access to the NPU terminology in English is currently at <www.labterm.dk>, via the English download files from the Danish Release Centre under the National Board of Health. Updates to the terminology are usually presented once a month.